2017
DOI: 10.4103/jrms.jrms_833_16
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired methicillin-resistant Staphylococcus aureus carriage rate and antimicrobial susceptibility in a tertiary center, Iran

Abstract: Background:This study was aimed to determine frequency and antimicrobial susceptibility of Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) among colonized patients in outpatient status.Materials and Methods:A total of 2000 nasal nares specimens were collected and inoculated on mannitol salt agar. MRSAs were identified based on mannitol positivity and coagulase test followed by cefoxitin disc diffusion test. Antimicrobial susceptibility of MRSA isolates was performed by E-test method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This might be attributed to many reasons like vancomycin which had been used rarely in Iraq during the United Nation's sanction period from 1990 to 2003; the drug was expensive and was not available in many health facilities. Also, our result was in accordance with the results of neighboring countries (Udo et al, 2009;Dangnew et al, 2012;Shokouhi et al, 2017). In contrast, Alsamarai et al, (2015) revealed that the 18.6% of studied food workers in Samara restaurants had vancomycinresistant S. aureus and Loeto et al, (2017) found that 27.3% of food handlers with MRSA also were resistant to vancomycin; this rate is near to that of the study done in Maharashtra among food handlers working in medical college restaurant (26.5%) (Kasturwar andShafee, 2011).…”
Section: Prevalence Of Vrsasupporting
confidence: 93%
See 2 more Smart Citations
“…This might be attributed to many reasons like vancomycin which had been used rarely in Iraq during the United Nation's sanction period from 1990 to 2003; the drug was expensive and was not available in many health facilities. Also, our result was in accordance with the results of neighboring countries (Udo et al, 2009;Dangnew et al, 2012;Shokouhi et al, 2017). In contrast, Alsamarai et al, (2015) revealed that the 18.6% of studied food workers in Samara restaurants had vancomycinresistant S. aureus and Loeto et al, (2017) found that 27.3% of food handlers with MRSA also were resistant to vancomycin; this rate is near to that of the study done in Maharashtra among food handlers working in medical college restaurant (26.5%) (Kasturwar andShafee, 2011).…”
Section: Prevalence Of Vrsasupporting
confidence: 93%
“…Lower MRSA rate 9.8% was reported among food handlers working in Gondar university in Ethiopia (Dagnew et al, 2012). (Shokouhi et al, 2017) found that only 1.25% of the studied population in the tertiary outpatient center in Iran had MRSA. In contrary to our study, no cases of MRSA were detected by other studies (Castro et al, 2016;Vatansever et al, 2016).…”
Section: Prevalence Of Mrsamentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, only one isolate had the pvl gene, and of 7 MRSA isolates, only one was positive for SCCmecV. [18] Of 202 S. aureus isolates collected in Chinese hospitals, SCCmec and pvl gene were observed in 10 isolates, and three of these were harbored SCCmecV. [19] In this study, of 93 isolates of S. aureus, 44 (47.82%) were found to be MRSA.…”
Section: Discussionmentioning
confidence: 55%
“…Globally, over 90% of Staphylococcus aureus are resistant to penicillin (Lowy 2003). Globally for general communities, MRSA colonization rate is 1.25%, accounting for 5.68% of isolated S. aureus (Shokouhi et al 2017). In Hajj, the reported rates are slightly higher; MRSA colonization is 1.46%, accounting for 7.1% of noninvasive S. aureus isolates in Hajj (Memish et al 2006).…”
Section: Drug Resistant Respiratory Infections In Hajjmentioning
confidence: 99%